2013
DOI: 10.7717/peerj.72
|View full text |Cite
|
Sign up to set email alerts
|

Palm-based diacylglycerol fat dry fractionation: effect of crystallisation temperature, cooling rate and agitation speed on physical and chemical properties of fractions

Abstract: Fractionation which separates the olein (liquid) and stearin (solid) fractions of oil is used to modify the physicochemical properties of fats in order to extend its applications. Studies showed that the properties of fractionated end products can be affected by fractionation processing conditions. In the present study, dry fractionation of palm-based diacylglycerol (PDAG) was performed at different: cooling rates (0.05, 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0°C/min), end-crystallisation temperatures (30, 35, 40, 45 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
3
4
0
Order By: Relevance
“…Hence, at a temperature of ≤38 °C, SFA have sufficient time to crystallize, which leads to better separation. Similar findings were found in studies carried out by Ab Latip et al (2013) and Huey et al (2009). In Latip's study, iodine value (IV) was used to determine the degree of saturation in fractionated samples.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Hence, at a temperature of ≤38 °C, SFA have sufficient time to crystallize, which leads to better separation. Similar findings were found in studies carried out by Ab Latip et al (2013) and Huey et al (2009). In Latip's study, iodine value (IV) was used to determine the degree of saturation in fractionated samples.…”
Section: Resultssupporting
confidence: 91%
“…The USFA content in olein phase under slow cooling rate is 63.34% ± 2.09, which was significantly ( P < 0.05) higher than the rapid cooling rate with USFA of 58.81% ± 0.06. Comparable results were reported in a study carried out by Ab Latip et al (2013), showing the correlation between IV value of olein fraction with the cooling rate. In the mentioned study, a fast cooling rate leads to the reduction in IV value of olein fraction, demonstrating that there are more SFA in liquid fraction.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…However, by decreasing the fractionation temperatures from 17 to 16.6 °C and in presence of 5% PO, the yields of PSO were decreased while PMF yields were increased. These results agree with that recorded by Calliauw et al, and Ablatip et al, [15,16] they found that the SF yield is strongly dependent on crystallization temperature, as crystallization temperature increased, the SF yield decreased and vice versa.…”
Section: Physical Properties Of Pol and Its Fractionssupporting
confidence: 93%
“…The results corresponded with the previous study conducted by Jin, Wang, Su et al (2017), where the yield of mango seed fat solid fractions decreased after first and second stages of fractionation due to the solid fractions became more saturated. The presence of high melting saturated fatty acids (SFAs) which were mainly arachidic and stearic acids in F 1 -S resulted in gradual precipitation of SFAs from the liquids because of the effect of low-temperature crystallization, hence more of solid fractions yielded (Latip et al, 2013). Meanwhile, the liquid fractions were found to be easily melted at <28°C due to the presence of low melting unsaturated fatty acids (USFAs) which were mainly oleic and linoleic acids causing less production of solid fractions at low temperature of crystallization process in the second stage of fractionation from F 1 -L (Jin, Wang, Su et al, 2017).…”
Section: Discussionmentioning
confidence: 99%